Intracellular Water Lifetime as a Tumor Biomarker to Monitor Doxorubicin Treatment via FFC-Relaxometry in a Breast Cancer Model - Ruggiero, Maria Rosaria; Baroni, Simona; Bitonto, Valeria; Ruiu, Roberto; Rapisarda, Smeralda; Aime, Silvio; Geninatti Crich, Simonetta (Frontiers in Oncology, 2021)
This study aims to explore whether the water exchange rate constants in tumor cells can act as a hallmark of pathology status and a reporter of therapeutic outcomes. It has been shown, using 4T1 cell cultures and murine allografts, that an early assessment of the therapeutic effect of doxorubicin can be detected through changes in the cellular water efflux rate constant kio. The latter has been estimated by analyzing the magnetization recovery curve in standard NMR T1 measurements when there is a marked difference in the proton relaxation rate constants (R1) between the intra- and the extra-cellular compartments. In cellular studies, T1 measurements were carried out on a relaxometer working at 0.5 T, and the required difference in R1 between the two compartments was achieved via the addition of a paramagnetic agent into the extracellular compartment. For in-vivo experiments, the large difference in the R1 values of the two-compartments was achieved when the T1 measurements were carried out at low magnetic field strengths. This task was accomplished using a Fast Field Cycling (FFC) relaxometer that was properly modified to host a mouse in its probe head. The decrease in kio upon the administration of doxorubicin is the result of the decreased activity of Na+/K+-ATPase, as shown in an independent test on the cellular uptake of Rb ions. The results reported herein suggest that kio can be considered a non-invasive, early and predictive biomarker for the identification of responsive patients immediately from the first doxorubicin treatment.